Marko Jesenšek: The Slovene Language in the Alpine and Pannonian Language Aria. The history of the Slovene Language. - Natalija Ulčnik (Slavia Centralis, 2020)
Avtorica prispevka predstavlja monografijo The Slovene Language in the Alpine and Pannonian Language Aria s podnaslovom The history of the Slovene Language avtorja Marka Jesenška.